Spiritual Piety and Social Piety: Sufism Teachings in the Modern Era and in the midst of the Covid-19 Virus Outbreak in Building a New Civilization - Siswoyo Aris Munandar (Sunan Kalijaga: International Journal of Islamic Civilization, 2021)
Sufism is a spiritual teaching that focus on worship as such rather than social life. The sufi are often regarded as anti-social, such as uzlah, seclusion, and zuhud. Is this true? The current paper urgues that it is not always true. The Idrisiyyah Order for example developed the Qini Mart business, Qini Minang (Padang restaurant), Qini Bakery (bread sales), Qini Fresh (refill drinking water depot), Islamic boarding school canteen, livestock, shrimp ponds in Cipatujah, Coffee plantations in Panjalu, and restaurants in cooperation with Islamic Boarding Schools. They established batul maal wat-tamwiil to run their businesses. In addition, in the case of Covid-19 out break, they introduce uzlah teaching or seclusion to reduce the transmission of Covid-19.